Exploring friendly AI interactions: A response to Li’s problems with friendly AI - Dinglasan, Joseph JP Christian E. (Animo Repository, 2024)
Barbro Fröding and Martin Peterson take a virtue-ethics approach in defending the claim that social AIs should be programmed to behave in a manner that mimics a sufficient number of aspects of proper friendship, which they later refer to as Friendly AI. The justification for this approach relies on two arguments: (1) treating AIs as slaves is morally wrong, and (2) the features of a Friendly AI would allow for such interaction that helps in the promotion and development of the human user’s virtues. A Friendly AI is expected to inform the human user of their behavior and provide opportunities for the human user to practice virtuous behavior. While agreeing that AIs should be programmed to behave in a friendly manner, Oliver Li identifies four with the implementation of Friendly AI systems through a virtue ethics approach. These problems emphasize the role of the human user and their needs in moral development. Following Li, I examine the virtue-ethical approach to formulate an account of how virtue is cultivated through interactions with Friendly AI. I argue that Li’s concerns are due to the examples provided by Fröding and Peterson of interactions with Friendly AI being limited to mostly one-on-one interactions. Activities that cultivate virtue are not limited to one-on-one interactions. From this, I propose that studies be made which explore interactions with Friendly AI such as those which involve other humans or AIs. Pursuing these studies would help us form a better understanding of how Friendly AIs can help develop virtues.